Exploring young people's perspectives on mental health support: A qualitative study across three geographical areas in England, UK. (25th October 2022) - Holding, Eleanor; Crowder, Mary; Woodrow, Nicholas; Griffin, Naomi; Knights, Nicky; Goyder, Elizabeth; McKeown, Rachael; Fairbrother, Hannah
Abstract: Improving young people's (YP) mental health and well‐being is a global public health priority. Despite continued commitment within the UK policy agenda to improve the mental health and well‐being of YP, the incidence of mental health issues continues to rise. This has been further compounded by the outbreak of COVID‐19 which has disproportionately affected YP in the most socioeconomically disadvantaged areas. Understanding YP's perspectives on what supports their mental health is important to develop policies that meet their needs. We conducted focus groups ( n  = 18 with 42 YP aged 13–21) in three geographical areas with high levels of deprivation in England, UK. Recruited through six local youth organisations, each group of YP took part in three interlinked focus groups designed to explore their perceptions of what impacts their health in their local area, and their understandings of health inequalities through participatory methods. Throughout their discussions, YP foregrounded the significance of mental health and mental health support structures. YP perceived challenges to accessing mental health provision and an unmet need for support within their local communities. Alongside this, YP consistently highlighted the importance of youth groups for promoting good mental health and mitigating challenges to poor mental health. However, ongoing cuts to the voluntary sector and universal services continue to impact areas and individuals in the greatest need. In the face of deficits in formal mental health support, our findings highlight the pressing need for increased investment in services focused on prevention (such as youth groups) in areas of high deprivation.